EVALUASI EFEKTIVITAS SERVANT LEADERSHIP DAN MOTIVASI KERJA TERHADAP KINERJA PERSONIL SATPAS DALAM MENINGKATKAN PELAYANAN PENERBITAN SIM DI WILAYAH HUKUM POLRESTABES PALEMBANG - Novi Indah Earlyanti; Fausiah Tamal; Yoeliastuti (POLITEKNIK LP3I JAKARTA, 2025)
This research is motivated by the quality of the National Police's Human Resources (HR) and public services which are not yet optimal, Standard Operating Procedures (SOP) which are still complicated, vocational school-based assessments which are still not running well, the integrity of officers is weak, and leadership style is something that must continue to be improved in the SIM service. The purpose of this research is to determine the evaluation of the effectiveness of servant Leadership and work motivation on the performance of Satpas personnel in improving SIM issuance services in the Palembang Police Legal Area. The concept or theory of Servant Leadership (X1) from Yulk (2016:62), work motivation (X2) is explained by Uno's theory (2017:53) and performance (Y) uses Robbins' theory (2015:76). This research uses quantitative methods with a cross-sectional research design. The target population in this research is the Palembang Police Traffic Unit personnel, 176 people who work at the Palembang Police. Meanwhile, the target population is 36 Satpas personnel. The data collection technique uses a 50-item questionnaire with a Likert scale. The data analysis technique used is Multiple Linear Regression Analysis. The research results show that the calculated F value is 425.013 with a significance level of 0.000. The t value is 7.538 with a significance value between Servant Leadership and the performance of Satpas personnel in improving SIM issuance services of 0.000. The multiple linear regression equation is ????̂ = 0.453 + 0.615X1 + 0.241